2022
DOI: 10.7150/thno.72465
|View full text |Cite
|
Sign up to set email alerts
|

How to improve photodynamic therapy-induced antitumor immunity for cancer treatment?

Abstract: Photodynamic therapy (PDT) is a promising method of tumor ablation and function-preserving oncological intervention, which is minimally invasive, repeatable, and has excellent function and cosmetic effect, with no cumulative toxicity. More importantly, PDT can induce immunogenic cell death and local inflammation, thus stimulating the body's immune response. However, the weak immunity induced by PDT alone is insufficient to trigger a systemic immune response towards cancer cells. To overcome this obstacle, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 126 publications
0
28
0
Order By: Relevance
“…Photodynamic therapy not only targets neoplastic cells and tumor blood vessels, but also activates the immune system to induce inflammation and immune response to tumor cells (123). Although the intrinsic cellular mechanisms of resistance to PDT have been characterized, the emerging importance of the TME and the inflammatory/immune antitumor response is currently under investigation (123,124). The specific role of CAFs and TAMs as an extrinsic mechanism of PDT resistance is attracting the attention for of researchers and is summarized in Table 1.…”
Section: The Tumor Microenviroment As Mediator Of Photodynamic Resist...mentioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy not only targets neoplastic cells and tumor blood vessels, but also activates the immune system to induce inflammation and immune response to tumor cells (123). Although the intrinsic cellular mechanisms of resistance to PDT have been characterized, the emerging importance of the TME and the inflammatory/immune antitumor response is currently under investigation (123,124). The specific role of CAFs and TAMs as an extrinsic mechanism of PDT resistance is attracting the attention for of researchers and is summarized in Table 1.…”
Section: The Tumor Microenviroment As Mediator Of Photodynamic Resist...mentioning
confidence: 99%
“…In the TME, uncontrolled cell proliferation avoid the ability to satisfy the oxygen demand from the preexisting blood vessels. Hypoxia has been found to directly regulate the expression of not only macrophages but also of other immune cells such as MDSCs (123,127). In PDT, molecular oxygen is necessary, as a microenvironment of hypoxia could lead to treatment failure and drug resistance (126).…”
Section: Tams and Pdtmentioning
confidence: 99%
“…Over the past few decades, immunotherapy has emerged as a promising strategy for the treatment of malignant tumors by assisting tumor patients to restore and enhance their own immune functions to combat tumors. Recent studies have shown that photosensitizer-based photodynamic therapy (PDT) could cause the production of reactive oxygen species (ROS), which could trigger an immunogenic cell death (ICD) effect to enhance the immunogenicity of tumor cells, ultimately promoting the infiltration of cytotoxic T lymphocytes (CTLs) and eliciting immune responses. However, PDT alone can only exert a limited immunotherapeutic effect due to the various defense mechanisms of tumors. For instance, ROS generated by PDT are rapidly scavenged by high levels of glutathione (GSH) in tumor cells to maintain intracellular redox homeostasis, thus weakening the ICD effect and preventing tumors from significantly increasing immunogenicity. , In addition, the immunosuppressive tumor microenvironment (ITM) favors the infiltration of immunosuppressive cells, including tumor-associated macrophages (TAMs), tumor-associated neutrophils, and myeloid-derived suppressor cells, which inhibit the immunotherapeutic effect triggered by PDT alone. Therefore, a simple strategy that can simultaneously disrupt redox homeostasis and reverse the tumor immunosuppressive microenvironment is crucial to enhance the immunotherapeutic effect of PDT.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these defects of mono-immunotherapy, combinational therapy such as immuno-photodynamic therapy (IPDT) has become a revolutionary approach, due to the increasing number of studies which have confirmed that PDT could initiate an antitumor immune response by the immunogenic cell death (ICD) mechanism . This approach is expected to offset the shortfalls of each mode of therapy and elicit an intact immune system for cancer treatment, which can not only bring strong immunogenicity for immunotherapy but also inhibit the growth of remaining tumor cells in the body left behind after PDT . During IPDT, the photosensitizers were excited by light in the presence of oxygen to generate reactive oxygen species (ROS) which could lead to apoptosis, necroptosis, pyroptosis, and microvascular damage, and then the dying cells induced ICD by releasing the damaged-associated molecular patterns (DAMPs), tumor-specific antigens, and proinflammatory cytokines, which could lead to more immunogen exposure and activation of the immune system. These biological events, similar to in situ “tumor vaccine”, enhance the tumor infiltration of immune cells and amplify the antitumor immune responses against solid tumors. , …”
Section: Introductionmentioning
confidence: 99%